2022
DOI: 10.1128/msystems.01505-21
|View full text |Cite|
|
Sign up to set email alerts
|

Label-Free Raman Microspectroscopy for Identifying Prokaryotic Virocells

Abstract: Viruses are highly diverse biological entities shaping many ecosystems across Earth. However, understanding the infection of individual microbial cells and the related biochemical changes remains limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Another promising approach could be Raman microspectroscopy for identification of infected Ca. A. hamiconexum cells [57] and its coupling to embedding and transmission electron microscopy (TEM). While these approaches are based on correlative microscopy, traditional immunogold labeling of viral proteins in MSI biofilms will eventually lead to the discovery of the actual virion structure visualized by TEM.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising approach could be Raman microspectroscopy for identification of infected Ca. A. hamiconexum cells [57] and its coupling to embedding and transmission electron microscopy (TEM). While these approaches are based on correlative microscopy, traditional immunogold labeling of viral proteins in MSI biofilms will eventually lead to the discovery of the actual virion structure visualized by TEM.…”
Section: Discussionmentioning
confidence: 99%
“…Monsees et al identified the Raman peak intensity ratio between nucleic acids and proteins useful for classification of virally infected cells from that of uninfected. They used Raman micro-spectroscopy for collecting the Raman signal from the phi6 (bacteriophage) infected Pseudomonas syringae and phi29 infected Bacillus subtilis as well as corresponding controls (Monsees et al 2022 ). They observed an increase in the ratio for the former case and a decrease in the latter.…”
Section: Raman Spectroscopy In Viral Diagnosticsmentioning
confidence: 99%